Isolation, Preliminary Enzyme Characterization and Optimization of Culture Parameters for Production of Naringinase Isolated from Aspergillus niger BCC 25166 - Kanokpan Thammawat; Pongsuda Pongtanya; Vitchuporn Juntharasri; Patjaraporn Wongvithoonyaporn (Agriculture and Natural Resources, 2008)
From isolation of fungi capable of hydrolyzing naringin by growing the fungi at 28°C on selective synthetic minimal medium, pH 5.8, containing 0.1% naringin, 348 fungi were isolated from 128 various host samples, collected from 11 different sources in Thailand and China. Primary screening of all 348 fungi was done by cultivation of the fungi at 40°C for 7 days in synthetic minimal medium, pH 4.0, added with 0.1% naringin, and by investigation of the naringin hydrolysis of the fungal culture filtrate at pH 4.0, 40°C, for 23-48 hours. Forty fungal isolates were obtained. Secondary screening was performed by measurement of both glycosidase activities, α-L-rhamnosidase and β-D-glucosidase at 40°C, pH 4.0, and naringinase activity at the temperatures of 50, 55 and 60°C and at both pH 3.0 and 4.0 of the culture filtrates from all 40 fungal isolates. Aspergillus niger BCC 25166 was selected and genetically identified. The optimum pH and temperature of the enzyme in crude extract were investigated. The result showed that all naringinase, α-L-rhamnosidase and β-D-glucosidase activities had identical optimum pH of 4.0. However, the optimum temperature of naringinase and α-L-rhamnosidase was 60°C, whereas that of β-D-glucosidase activity was in the range of 60° to 70°C. Optimization of the medium and conditions for enzymes production in submerged fermentation found that the suitable inoculum concentration and medium were 105 spores/ml and Czapek-Dox medium, pH 4.0, containing 0.1% naringin, respectively. The maximum naringinase production of this fungus (117.77 U/mg protein) could be obtained by supplement of the medium with 3.75 g/l rhamnose as another carbon source and using 2.5 g/l NaNO3 as its nitrogen source. For high production of α-L-rhamnosidase (303.20 U/mg protein), 2.5 g/l soya peptone should be used instead.